KETIDAKADILAN DALAM PEMBAGIAN HARTA GONO GINI PADA KASUS PERCERAIAN - Sri Hariati (Jurnal Restorative Justice, 2020)
After the divorce, it does not mean that all family's problems have been resolved. Thereleaves the remaining of marital problems such as children (if the couple have children) and property which obtained during marriage. These assets obtained during marriage is called joint property or better known as Gono Gini assets. Disputes over the distribution of joint assets in general, it can be illustrated as the resolution of disputes over sharing of joint assets. This process of sharing Gono Gini’s assets in a divorce case often creates injustice in various aspects, especially in the distribution of shared assets (Gono Gini assets). The method used in this research is that is a qualitative approach with a descriptive narrative method. Data collection in this study ranging from observations, interviews, and and references obtained from various sources in Suralaga Village, Suralaga District. The results of research conducted on the injustice distribution of joint assets in Suralaga Village, Suralaga District, East Lombok Regency shows that Injustice that occurs in the process of sharing joint assets aftee divorce is caused by several factors. Those factors are including the patriarchal ideology culture that is still developing until today. In addition, the injustice that occurs is caused by inheritance legal system which become the basis of decision making. That legal system is indicating discrimination against the existence of women as the dominant party who gets injustice in the process of sharing joint property. so that, this injustice happens as the form of current policy.